Diffusion of a micronutrient home fortification program for infants and toddlers in a multi-ethnic population in rural western China - Ruixue Ye; Yuju Wu; Chang Sun; Qingzhi Wang; Yuping Mao; Huan Zhou; Hein Raat (BMC, 2023)
Abstract Background The micronutrient home fortification programs contribute to the prevention of childhood anemia. WHO suggested applying culturally appropriate strategies to implement the micronutrient home fortification programs in various communities. However, there is little knowledge on evidence-based effective diffusion strategies of the micronutrient home fortification programs in multi-ethnic populations. This study aims to examine the diffusion of a micronutrient home fortification program with micronutrient powder (MNP) in a multi-ethnic population by investigating factors associated with being an 'early' or a 'later' adopter of MNP. Methods We conducted a cross-sectional study in rural western China. Multistage sampling was used to select children's caregivers in Han, Tibetan, and Yi ethnic communities (N = 570). The diffusion of innovations theory informed the data collection on caregivers' decision process and was applied to classify participants into the MNP adopter categories of 'leaders', 'followers', 'loungers', and 'laggards'. The ordered logistic regression model estimated the factors associated with the MNP adopter categories. Results Caregivers from the Yi ethnic subgroup were likely to adopt MNP relatively late (AOR = 1.67; 95%CI = 1.09, 2.54) compared with Han and Tibetan ethnic subgroups. Caregivers with more knowledge regarding the MNP feeding method (AOR = 0.71; 95%CI = 0.52, 0.97) and those with stronger self-efficacy in adopting MNP (AOR = 0.85; 95%CI = 0.76, 0.96) were more likely to adopt MNP earlier than others. The following messages and channels also tend to make caregivers adopt MNP earlier: hearing that 'MNP was free' from villagers (AOR = 0.45; 95%CI = 0.20, 0.98), and learning 'MNP feeding method' from township doctors (AOR = 0.16; 95%CI = 0.06, 0.48). Conclusions Disparities in adopting MNP existing among different ethnic groups require more effective diffusion strategies in disadvantaged minority ethnic groups. Enhancing self-efficacy in adopting MNP and knowledge on feeding method of MNP have the potential to make caregivers adopt MNP earlier. Peer networks and township doctors can be effective agencies to facilitate the diffusion and adoption of MNP.